Cytochrome b 5 impacts on cytochrome P450-mediated metabolism of benzo[a]pyrene and its DNA adduct formation: studies in hepatic cytochrome b 5 /P450 reductase null (HBRN) mice - Reed, Lindsay; Mrizova, Iveta; Bárta, František; Indra, Radek; Moserova, Michaela; Kopka, Klaus; Schmeiser, Heinz H; Wolf, C Roland; Henderson, Colin J; Stiborova, Marie; Phillips, David H; Arlt, Volker M (Archives of toxicology, 2018)
Benzo[a]pyrene (BaP) is an environmental pollutant that, based on evidence largely from in vitro studies, exerts its genotoxic effects after metabolic activation by cytochrome P450s. In the present study, Hepatic Reductase Null (HRN) and Hepatic Cytochrome b 5 /P450 Reductase Null (HBRN) mice have been used to study the role of P450s in the metabolic activation of BaP in vivo. In HRN mice, cytochrome P450 oxidoreductase (POR), the electron donor to P450, is deleted specifically in hepatocytes. In HBRN mice the microsomal haemoprotein cytochrome b 5 , which can also act as an electron donor from cytochrome b 5 reductase to P450s, is also deleted in the liver. Wild-type (WT), HRN and HBRN mice were treated by i.p. injection with 125 mg/kg body weight BaP for 24 h. Hepatic microsomal fractions were isolated from BaP-treated and untreated mice. In vitro incubations carried out with BaP-pretreated microsomal fractions, BaP and DNA resulted in significantly higher BaP-DNA adduct formation with WT microsomal fractions compared to those from HRN or HBRN mice. Adduct formation (i.e. 10-(deoxyguanosin-N2-yl)-7,8,9-trihydroxy-7,8,9,10-tetrahydro-BaP [dG-N2-BPDE]) correlated with observed CYP1A activity and metabolite formation (i.e. BaP-7,8-dihydrodiol) when NADPH or NADH was used as enzymatic cofactors. BaP-DNA adduct levels (i.e. dG-N2-BPDE) in vivo were significantly higher (~ sevenfold) in liver of HRN mice than WT mice while no significant difference in adduct formation was observed in liver between HBRN and WT mice. Our results demonstrate that POR and cytochrome b 5 both modulate P450-mediated activation of BaP in vitro. However, hepatic P450 enzymes in vivo appear to be more important for BaP detoxification than its activation.
Keywords: hepatocyty; jaterní mikrozomy; Hepatocytes; Animals; NADPH-Ferrihemoprotein Reductase; Cytochrome-B(5) Reductase; benzopyren; myši knockoutované; NADPH-cytochrom c-reduktasa; zvířata; adukty DNA; Mice; DNA Adducts; cytochrom-B(5)-reduktasa; Benzo(a)pyrene; Mice, Knockout; Microsomes, Liver; myši